Genomic insights into the evolution of secondary metabolism of Escovopsis and its allies, specialized fungal symbionts of fungus-farming ants - Berasategui, Aileen; Salem, Hassan; Moller, Abraham G.; Christopher, Yuliana; Montoya, Quimi Vidaurre [UNESP]; Conn, Caitlin; Read, Timothy D.; Rodrigues, Andre [UNESP]; Ziemert, Nadine; Gerardo, Nicole (American Society for Microbiology, 2024)
The metabolic intimacy of symbiosis often demands the work of specialists. Natural products and defensive secondary metabolites can drive specificity by ensuring infection and propagation across host generations. But in contrast to bacteria, little is known about the diversity and distribution of natural product biosynthetic pathways among fungi and how they evolve to facilitate symbiosis and adaptation to their host environment. In this study, we define the secondary metabolism of Escovopsis and closely related genera, symbionts in the gardens of fungus-farming ants. We ask how the gain and loss of various biosynthetic pathways correspond to divergent lifestyles. Long-read sequencing allowed us to define the chromosomal features of representative Escovopsis strains, revealing highly reduced genomes composed of seven to eight chromosomes. The genomes are highly syntenic with macrosynteny decreasing with increasing phylogenetic distance, while maintaining a high degree of mesosynteny. An ancestral state reconstruction analysis of biosynthetic pathways revealed that, while many secondary metabolites are shared with non-ant-associated Sordariomycetes, 56 pathways are unique to the symbiotic genera. Reflecting adaptation to diverging ant agricultural systems, we observe that the stepwise acquisition of these pathways mirrors the ecological radiations of attine ants and the dynamic recruitment and replacement of their fungal cultivars. As different clades encode characteristic combinations of biosynthetic gene clusters, these delineating profiles provide important insights into the possible mechanisms underlying specificity between these symbionts and their fungal hosts. Collectively, our findings shed light on the evolutionary dynamic nature of secondary metabolism in Escovopsis and its allies, reflecting adaptation of the symbionts to an ancient agricultural system. IMPORTANCE Microbial symbionts interact with their hosts and competitors through a remarkable array of secondary metabolites and natural products. Here, we highlight the highly streamlined genomic features of attine-associated fungal symbionts. The genomes of Escovopsis species, as well as species from other symbiont genera, many of which are common with the gardens of fungus-growing ants, are defined by seven chromosomes. Despite a high degree of metabolic conservation, we observe some variation in the symbionts’ potential to produce secondary metabolites. As the phylogenetic distribution of the encoding biosynthetic gene clusters coincides with attine transitions in agricultural systems, we highlight the likely role of these metabolites in mediating adaptation by a group of highly specialized symbionts.
Keywords: parasitism; secondary metabolism; symbiosis